Inhibitory action of a non-metabolizable fatty acid on the growth of Escherichia coli: role of metabolism and outer membrane integrity. - Fay, J P (1977)
The inhibitory action of decanoic acid on both Escherichia coli K-12/154 (normal lipopolysaccharide) and E. coli RC59 (defective lipopolysaccharide) was studied. A correlation was found between the doubling time of E. coli 154 growing in different media and the lethal effect of 0.4% decanoic acid on this bacterium. Decanoic acid (0.4%) exerted a lytic action on glucose-starved and NaN3-inhibited cells of E. coli 154 and RC59. Exponentially growing cultures of both strains were not affected by the addition of 0.4% methyldecanoate, but cells of E. coli RC59 reaching the stationary phase were attacked by that compound. A bactericidal action of 0.4% methyldecanoate on exponential E. coli 154 and RC59 was observed when sodium azide was also present in the media. Concentrations lower than 0.01% methyldecanoate had a lytic effect on spheroplasts from E. coli 154 and RC59. These results indicate that the inhibitory action of a non-metabolizable fatty acid on E. coli depends on the cellular metabolic activity and the outer membrane integrity.